2007
DOI: 10.1128/iai.01999-06
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Immune Responses to Mycobacterium tuberculosis DosR Regulon Proteins following Mycobacterium bovis BCG Vaccination

Abstract: Mycobacterium bovis BCG is widely used as a vaccine against tuberculosis (TB),Tuberculosis (TB) remains a major global health threat. Each year, about eight million new TB cases occur and two million people die from TB. It is estimated that one-third of the world population is latently infected with Mycobacterium tuberculosis. From this vast latent reservoir, about 10% of infected people are expected to develop overt TB disease during their lifetimes. However, with the expanding human immunodeficiency virus ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 42 publications
(47 reference statements)
4
74
0
Order By: Relevance
“…In this context, it is noteworthy that other studies also have reported reactivity to MTB-encoded antigens in HCs and NTM-infected/exposed individuals that is hypothesized to be as a result of exposure to NTMs (7,8,31). Furthermore, NTM exposure may explain the higher baseline reactivity to PPD that was found in MTB-naive young adults as compared with children (32).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this context, it is noteworthy that other studies also have reported reactivity to MTB-encoded antigens in HCs and NTM-infected/exposed individuals that is hypothesized to be as a result of exposure to NTMs (7,8,31). Furthermore, NTM exposure may explain the higher baseline reactivity to PPD that was found in MTB-naive young adults as compared with children (32).…”
Section: Discussionmentioning
confidence: 74%
“…For example, a population in Malawi with no history or scar evidence of prior bCG vaccination or MTB infection showed responsiveness to a variety of mycobacterial antigens and purified protein derivative (PPD) from different NTMs (5,6). In addition, non-MTB-infected and non-bCG-vaccinated individuals respond to MTB-encoded antigens, MTB lysate, and PPD (7,8).…”
mentioning
confidence: 99%
“…Consequently, novel concepts have been investigated that include the use of different epitopes of RD antigens [11,12,36,37,58], readout different from IFN-c such as chemokines or cytokines [56,58], new antigens different from the RD genomic region, such as those defined as Rv1733c, Rv2029c, Rv2032, Rv2626c, Rv2627c, Rv2628 and HspX [29,[59][60][61], additional cytokines [56] or characteristic phenotypic markers [11,12,36,62]. Diagnostic sensitivity of IGRA can also be enhanced by incorporation of a novel RD1-encoded antigen, Rv3879c, without compromising diagnostic specificity [63].…”
Section: Sectionmentioning
confidence: 99%
“…Endotoxin contents were ,50 IU/ mg as tested using a Limulus amebocyte lysate assay (Cambrex, East Rutherford, NJ). All recombinant proteins were tested in lymphocyte stimulation assays to exclude Ag nonspecific T cell stimulation and cellular toxicity using PBMC of in vitro-purified protein derivative of M. tuberculosis-negative healthy Dutch donors (Sanquin Blood Bank, Leiden, The Netherlands) (12,(40)(41)(42). Purified protein derivative of M. tuberculosis was purchased from Statens Serum Institute.…”
Section: Recombinant Proteinsmentioning
confidence: 99%